A Versatile Synthetic Pathway for Producing Mesostructured Plasmonic Nanostructures. Issue 47 (21st October 2022) - Kim, Sejung; Palani, Stephen; Civitci, Fehmi; Nan, Xiaolin; Ibsen, Stuart
Abstract: Highly branched gold (Au) nanostructures with sharp tips are considered excellent substrates for surface‐enhanced Raman scattering (SERS)‐based sensing technologies. Here, a simple synthetic route for producing Au or Au‐Ag bimetallic mesostructures with multiple sharpened tips in the presence of carbon quantum dots (CQDs) is presented. The morphologies of these mesostructured plasmonic nanoparticles (MSPNs) can be controlled by adjusting the concentration of CQDs, reaction temperatures, and seed particles. The optimal molar ratio for [HAuCl4 ]/[CQDs] is found to be ≈25. At this molar ratio, the diameters of MSPNs can be tuned from 80 to 200 nm by changing the reaction temperature from 25 to 80 °C. In addition, it is found that hierarchical MSPNs consisting of multiple Au nanocrystals can be formed over the entire seed particle surface. Finally, the SERS activity of these MSPNs is examined through the detection of rhodamine 6G and methylene blue. Of the different mesostructures, the bimetallic MSPNs have the highest sensitivity with the ability to detect 10 −7 m of rhodamine 6G and 10 −6 m of methylene blue. The properties of these MSPN particles, made using a novel synthetic process, make them excellent candidates for SERS‐based chemical sensing applications. Abstract : Development of a carbon quantum dot‐assisted synthetic pathway to produce various types of mesostructured plasmonic nanoparticles (MSPNs), resulting in sphere, rod, triangle, and cube structures. Additional synthetic pathways are developed for bimetallic structures based on Au‐Ag. The bimetallic MSPNs have the best surface‐enhanced Raman scattering performance with detection of rhodamine 6G at 10 −7 m .